2015
DOI: 10.1038/mp.2015.56
|View full text |Cite
|
Sign up to set email alerts
|

Small molecules demonstrate the role of dynamin as a bi-directional regulator of the exocytosis fusion pore and vesicle release

Abstract: Hormones and neurotransmitters are stored in specialised vesicles and released from excitable cells through exocytosis. During vesicle fusion with the plasma membrane, a transient fusion pore is created that enables transmitter release. The protein dynamin is known to regulate fusion pore expansion (FPE). The mechanism is unknown, but requires its oligomerisation-stimulated GTPase activity. We used a palette of small molecule dynamin modulators to reveal bi-directional regulation of FPE by dynamin and vesicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 58 publications
6
59
0
Order By: Relevance
“…Dyngo-4a, on the other hand, acted post chemokine receptor binding at a time point late in the fusion reaction suggesting that dynamin in its lipid bound helical oligomer can regulate the final stages of HIV fusion through fusion pore expansion. Support for this process is observed in regulation of exocytic fusion pore dynamics, where the use of dyngo-4a resulted in pore restriction and reduced vesicle release [60]. Dynamin's role in HIV-fusion reaction is further supported in a recent study by Jones and colleagues wherein using fluorescently tagged dynamin and dual labelled HIV virions.…”
Section: Role Of Dynamin In Hiv Entrymentioning
confidence: 88%
See 1 more Smart Citation
“…Dyngo-4a, on the other hand, acted post chemokine receptor binding at a time point late in the fusion reaction suggesting that dynamin in its lipid bound helical oligomer can regulate the final stages of HIV fusion through fusion pore expansion. Support for this process is observed in regulation of exocytic fusion pore dynamics, where the use of dyngo-4a resulted in pore restriction and reduced vesicle release [60]. Dynamin's role in HIV-fusion reaction is further supported in a recent study by Jones and colleagues wherein using fluorescently tagged dynamin and dual labelled HIV virions.…”
Section: Role Of Dynamin In Hiv Entrymentioning
confidence: 88%
“…While dynamin 2 is ubiquitously expressed, the expression of dynamin 1 is largely restricted to neurons while dynamin 3 is found in brain and testis [55][56][57]. In addition to its role in CME, dynamin can also mediate membrane fission [58], interact with cytoskeletal F actin, promote tethering and hemi-fusion of membranes [28,59], lead to stabilization and expansion of fusion pores [28,60] and regulate cytokinesis by concentrating at sites of abscission [61][62][63]. Each of these roles has the potential to influence HIV infection at various stages of virus life cycle from entry to progression of infection through cell cycle and is independent of the process of endocytosis.…”
Section: Role Of Dynamin In Hiv Entrymentioning
confidence: 99%
“…Therefore, fusing vesicles remain connected to the plasma membrane with a narrow pore until the addition of new proteins and lipids to the fusion machinery reverses the process. Indeed, a variety of proteins, such as dynamin (Anantharam et al, 2011; Jackson et al, 2015), myosin II, actin (Aoki et al, 2010), SNARE proteins (Fang et al, 2008; Gucek et al, 2016), synaptotagmin (Wang et al, 2001; Lai et al, 2013), and complexin (Dhara et al, 2014) have been found to affect the fusion pore dynamics in chromaffin and PC12 cells. These studies highlight an active role of these components in impacting the fusion pore.…”
Section: Exocytosis In Excitable Cellsmentioning
confidence: 99%
“…As a GTPase, the role of dynamin in mediating fission of endocytic vesicle is well-known. On the exocytosis side, transfecting PC12 cells with a dynamin mutant with elevated GTPase activity shortened the foot duration of amperometry recordings, while the opposite occurred with the overexpression of a dynamin mutant with reduced GTPase activity (Anantharam et al, 2011; Jackson et al, 2015). These experiments place dynamin at the very beginning of exocytosis regulation, where the fusion pore is smaller than 1 nm.…”
Section: Molecular Mechanisms For Exo-endocytosis Couplingmentioning
confidence: 99%
“…This interaction with the actin cytoskeleton is important for endocytic membrane retrieval and vesicle replenishment (e.g., Hayashida et al, 2015; Wen et al, 2016; Wu et al, 2016; Soykan et al, 2017; for review, see Rizzoli, 2014; Kononenko and Haucke, 2015; Soykan et al, 2016; Herrero-Garcia and O’Bryan, 2017). Besides its well-known essential role in vesicle fission, dynamin has been proposed to be involved in certain aspects of membrane fusion, e.g., fusion pore stabilization and expansion (Peters et al, 2004; Anantharam et al, 2011, 2012; Samasilp et al, 2012, 2014; Alpadi et al, 2013; González-Jamett et al, 2013; Kulkarni et al, 2014; Jackson et al, 2015; Zhao et al, 2016; for review, see Antonny, 2004; Sever et al, 2013; Quan and Robinson, 2014; Ren et al, 2016). In mammalian cells, dynamin-dependent tasks have to be accomplished by the gene products of three dynamin genes, dynamin1-3 (Cook et al, 1996; Urrutia et al, 1997; for review, see Ferguson and De Camilli, 2012).…”
Section: Introductionmentioning
confidence: 99%